THE PRODUCING OF ANALOG RICE BASED ON BANANA FLOUR (Musa paradisiaca) - Yudanti, Yolanda Risma (The University of Lampung, 2015)
Analog rice is one of the solutions that can be developed to overcome the problems of food security both in termsof the use of a new food source or for diversification of food. The purposes of this study were to determine theeffect of starch as a binder in the manufacture of analog rice and to examine the properties of analog rice in thetermofmoisture content, grains diameter,water absorption, bulk density, and expantion ability. Analog ricewasperformed by using a set of analog rice grain making machine (granulator). Five different compositions ofanalog rice weremade and tested. The formulas are pure bananas flour rice (100%banana flour) and mixed ofbanana flour and tapioca flour with ratio of 95 : 5, 90 : 10, 85 : 15 and 80 : 20. The results show that the watercontent of analog rice is between 10,41%and 13,08%, water absorption range from 36,98%to 64,32%, bulkdensity of 0,766 g /cm3 to 0,794 g /cm3, and expantion ability range from5,4%to 14,4%. The addition amountof the flourmixture causes enlargement of the grain diameter.Keywords: banana flour, tapioca flour, analog rice, granulator, diversification.